Z działalności Marii Skłodowskiej-Curie w Komisji Międzynarodowej Współpracy Intelektualnej Ligi Narodów (1922–1934) - Brzeziński, Andrzej M. (Przegląd Nauk Historycznych, 2006)
Activity of Maria Skłodowska-Curie on the International Committee on Intellectual Cooperation (CICI) of the League of Nations it was her only infidelity to scientific research. In 1922 Skłodowska-Curie agreed to work "temporarily" as a member of the CICI. As Professor of Physics at the University of Paris and Honorary Professor of the University of Warsaw she represented. after acceptance French authorities. Polish science in the CICI. From the beginning she appreciated the role of CICI on the international intellectual cooperation and attended almost all meetings as very active and diligent Committee member during her last twelve years of life. Skłodowska- Curie initiated creation the Sub-Committees CICI and direct contact with "national" committees on the intellectual cooperation. In September 1922 she presented to the League of Nations Council the report about the state of Polish science and her necessities. She tried to support the all initiatives towards the developing intellectual life in Poland. As a member of CICI. M. Skłodowska-Curie was interested the question of protecting scientific property rights. She appealed and made some projects for international funding of post-university research and also for international aid for universities. libraries. scholarships and laboratories. She joined the Sub-Committee on Bibliography in order to produce an international bibliographical index of the sciences. In 1931, after organizational reform international intellectual cooperation of the League of Nations. M. Skłodowska-Curie was elected Vice-president Intellectual Cooperation Organization. the member of the Executive Committee and Committee of Experts on Bibliography of the SCiences. In May 1933 Skłodowska- Curie presided over a public forum on the international conference in Madrid entitled "future of Culture" sponsored by the League of Nations.